Identifying subgroups of individuals undergoing metabolic bariatric surgery based on behavioral and psychosocial factors: A latent profile analysis - Ellen A. M. Kuipers; Josien G. Timmerman; Marc J. van Det; Marloes Vermeer; Miriam M. R. Vollenbroek - Hutten (PLoS ONE, 2026)
Purpose We performed a latent profile analysis (LPA) to identify subgroups in the population undergoing metabolic bariatric surgery (MBS), based on various behavioral and psychosocial characteristics. Gaining deeper insights into the variability among preoperative MBS patients may be helpful in facilitating tailored care that addresses the specific needs of each profile, in relation to physical, emotional, and psychological functioning. Methods Within a prospective cohort study, demographics and questionnaires regarding general health, quality of life, social support, problematic eating behavior (i.e., emotional eating, external eating, restrained eating, disordered eating) and depressive symptoms were collected preoperatively. LPA was performed to identify homogeneous subgroups. Results Out of 272 patients, four distinctive profiles were derived. The profiles were: (1) ‘ higher psychosocial and physical functioning profile’ (n = 122, 45%): no deficits on all domains; (2) ‘higher psychosocial and lower physical functioning’ (n = 53, 20%): moderate impairments in physical functioning and problematic eating behavior, with no to mild impairments in emotional wellbeing and high scores on social support; (3) ‘ lower psychosocial functioning and stable physical health’ (n = 36, 13%): mild impairments in physical functioning, with moderate levels of depressive symptoms and problematic eating behavior; (4) ‘ lower psychosocial and physical functioning profile’ (n = 61, 22%): moderate deficits in general health, problematic eating behavior, depressive symptoms, social support, and quality of life. Conclusion These findings suggest that subgroups can be identified, differing in behavioral and psychosocial characteristics, including psychological well-being, eating behavior, social support, and physical and emotional functioning among patients prior to MBS. Future longitudinal studies are necessary to establish the prognostic validity of these subgroups.